2020
DOI: 10.3390/vaccines8010033
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity against Vibrio harveyi in Grouper Induced by Single Vaccination with Poly (Lactide-co-glycolide) Microparticles Releasing Pleurocidin Peptide and Recombinant Glyceraldehyde-3-phosphate Dehydrogenase

Abstract: The peptide adjuvant, pleurocidin (PLE), and the Vibrio harveyi antigen, recombinant glyceraldehyde-3-phosphate dehydrogenase (rGAPDH) protein, were encapsulated with poly (lactide-co-glycolide) (PLG) polymers in our previous study to produce PLG-encapsulated PLE plus rGAPDH microparticles (PLG-PLE/rGAPDH MPs) that sustained stable release of both PLE and rGAPDH as well as, after two-time vaccination with MPs, generated long-term protective immunity against V. harveyi in grouper. Stable controlled-release of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Pleurocidins, may help protect fish populations as immune response modulators. Researchers have already developed effective vaccine strategies for fish against Vibrio harveyi , whereby the AMP and protein adjuvants are encased in polymers [ 63 , 64 ]. One study found pleurocidins to confer long-term immunity against V. harveyi in grouper by promoting lymphocyte proliferation and TNF-α [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pleurocidins, may help protect fish populations as immune response modulators. Researchers have already developed effective vaccine strategies for fish against Vibrio harveyi , whereby the AMP and protein adjuvants are encased in polymers [ 63 , 64 ]. One study found pleurocidins to confer long-term immunity against V. harveyi in grouper by promoting lymphocyte proliferation and TNF-α [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have already developed effective vaccine strategies for fish against Vibrio harveyi , whereby the AMP and protein adjuvants are encased in polymers [ 63 , 64 ]. One study found pleurocidins to confer long-term immunity against V. harveyi in grouper by promoting lymphocyte proliferation and TNF-α [ 64 ]. Another study attempted to use a pleurocidin promoter to protect against VHSV, but found the promotor did not induce an effective response compared to other promotors [ 65 ].…”
Section: Resultsmentioning
confidence: 99%